2003
DOI: 10.1046/j.0266-4909.2003.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and analysing activity and learning in virtual communities

Abstract: The purpose of this study is to provide a preliminary framework to observe, analyse and evaluate both activity and learning in virtual communities. So various types of virtual communities will be studied by examining their relationship to socialisation and learning. After a presentation of the main ideas of Wenger's social learning theory, the principal components of the social context of the emergence and evolution of virtual communities will be described. It will show how taking this context into account ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
1
18

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(125 citation statements)
references
References 11 publications
2
104
1
18
Order By: Relevance
“…Researchers categorize communities in different ways. For example, Henri and Pudelko (2003) identify four types of virtual communities: communities of interest, goal-oriented communities of interest, learners' community, and community of practice. Riel and Polin (2004) identify three types of learning communities: task-based, practice-based, and knowledge-based.…”
Section: Indd 244mentioning
confidence: 99%
“…Researchers categorize communities in different ways. For example, Henri and Pudelko (2003) identify four types of virtual communities: communities of interest, goal-oriented communities of interest, learners' community, and community of practice. Riel and Polin (2004) identify three types of learning communities: task-based, practice-based, and knowledge-based.…”
Section: Indd 244mentioning
confidence: 99%
“…According to Henri and Pudelko (2003), Blueplanet can capture all important characteristics [6]. First, Blueplanet is an open community for people to join.…”
Section: B Case Studymentioning
confidence: 99%
“…Knowledge usage refers to practical use, perceptual use, adaptive use, selective use, premature use, rejected use (i.e., deliberate nonuse), discontinued use, and misuse [5]. Knowledge usage is also meant to adaptive use, discontinued use, disuse, and misuse of knowledge, [6].…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Much of the educational research in this area has focused on examining the importance of teacher-student and student-student interaction in the online learning process, and in particular the use of discussion/bulletin boards to foster the creation of an effective learning environment (Downing & Chim, 2004a). While some of this research has suggested effective ways of creating such an environment (Chou, 2001;Henri & Pudelko, 2003;Gilbert & Dabbagh, 2005), relatively few studies (De Laat & Lally, 2004;Yukselturk & Top, 2006) have undertaken detailed week-on-week analysis of tutor and student bulletin board activity throughout a semester, and used these data to make recommendations about how an effective online learning community can be established with appropriate use of the discussion/ bulletin board tools in Blackboard and Web CT.…”
Section: Introductionmentioning
confidence: 99%